Teachers’ Occupational Well-being in the Era of Digitalisation: Resources, Competences, and Demands - Diganayeva, Aminat (ADA University, 2023)
The sudden outbreak of the COVID-19 pandemic in 2020 caused tremendous shifts in the delivery of education. Teachers were required to develop digital skills: they had to learn to manage online classes, use online tools, and change their way of communication. This sudden shift brought stressors too. Sitting in front of computers to manage online classes required teachers to be flexible, adaptable, and to adapt to new skills. How well teachers dealt with the new situation affected howlessons were delivered, making it necessary to look at occupational well-being considering recent innovations. To gain better insights into the topic, a systematic literature review within a conceptual framework is undertaken here. The framework encompasses physical and mental, cognitive, subjective, and social well-being. This paper argues that while having to use ICT could be overwhelming for teachers, the impact of technological integration may have positive, negative, and neutral impacts on educator’s well-being.
Keywords: Professional development; Quality teaching